Tailoring the lasing modes in semiconductor nanowire cavities using intrinsic self-absorption - Liu, Xinfeng (2013)
Understanding the optical gain and mode-selection mechanisms in semiconductor nanowire (NW) lasers is key to the development of high-performance nanoscale oscillators, amplified semiconductor/plasmon lasers and single photon emitters, and so forth. Modification of semiconductor band structure/bandgap through electric field modulation, elemental doping, or alloying semiconductors has so far gained limited success in achieving output mode tunability of the NW laser. One stifling issue is the considerable optical losses induced in the NW cavities by these extrinsic methods that limit their applicability. Herein we demonstrate a new optical self-feedback mechanism based on the intrinsic self-absorption of the gain media to achieve low-loss, room-temperature NW lasing with a high degree of mode selectivity (over 30 nm). The cadmium sulfide (CdS) NW lasing wavelength is continuously tunable from 489 to 520 nm as the length of the NWs increases from 4 to 25 μm. Our straightforward approach is widely applicable in most semiconductor or semiconductor/plasmonic NW cavities.